The Text4HealthyAging Program: An Evidence-Based Text Messaging Innovation to Support Healthy Urban Aging in Canada and Australia. (9th February 2022) - Eboreime, Ejemai; Ohinmaa, Arto; Rusak, Benjamin; Cassidy, Keri-Leigh; Morrison, Jason; McGrath, Patrick; Uher, Rudolf; Meier, Sandra; Fleury, Marie-Josee; Iyer, Srividya N.; Rej, Soham; Batchelor, Frances; et al.
Age-friendly cities are crucial to achieve the WHO goal of healthy aging. Such cities promote opportunities for health, participation, and security, thus enhancing quality of life as people age. Older people commonly experience psychosocial challenges such as anxiety, depression, substance abuse, loss of autonomy, grief, fear, and loneliness. Australian and Canadian cities continue to seek innovation to improve healthy urban aging and create more age-friendly environments for older adults. There is increasing evidence on the effectiveness and feasibility of mobile technology in health promotion and closing psychological treatment gaps. Older adults have been demonstrated to engage frequently with mobile devices, particularly text messaging. In this article, we conceptualize the Text4HealthyAging, an evidence-based text messaging innovation to support healthy urban aging in Canadian and Australian cities.